Novel Techniques in the Surgical Treatment of Acromegaly: Applications and Efficacy - Buchfelder, Michael; Schlaffer, Sven-Martin (Neuroendocrinology, 2016)
Since the establishment of transsphenoidal microsurgery as the operative treatment of choice in most patients with acromegaly 40 years ago, a few novel technical developments have evolved. Their application, utility and efficacy will be briefly discussed in this review article, based on an analysis of published results and the authors' personal experience. The endoscope was additionally used to search for residual tumours in locations which could not be visualised with the operating microscope. In many centres it has by now fully replaced the operating microscope. Extended endoscopic operations hardly have limits in respect to accessible pathology. Overall, the results and complications reported from microsurgical and endoscopic series are comparable. Intraoperative magnetic resonance imaging allows depicting the completeness of a tumour resection. While in many patients additional tumour resections are performed on the basis of intraoperative imaging, the improvements in hormonal remission rates reported are less impressive. Neuronavigation uses imaging data to improve the surgeon's orientation, and it is certainly a major asset to the inexperienced. In high-caseload centres it is mainly appreciated in anatomical variants and reoperations. While the Doppler probe is a valuable and easily affordable gadget to avoid vascular arterial injury, intraoperative ultrasound imaging of tumour extension has a much poorer resolution than magnetic resonance imaging and is thus not widely implemented. The clinical value of intraoperative growth hormone measurements is controversially discussed. In summary, the application of modern technology has only led to a minor improvement of results, but it has widened the spectrum of accessible pathologies and increased the safety of the procedures for the patient. It is expected that outcomes will continue to improve as novel techniques and concepts are being developed.
EVALuna2:22871